Juego de roles en el desarrollo socio emocional de niños en Educación Inicial 2 - Lombeida Chávez, Jessybel Paulette (2025)
The present study aims to determine the impact of role-playing games on the socio-emotional development of children in Early Childhood Education 2 at the Isabel la Católica Basic Education School. Within the early childhood classrooms, children have difficulties in their socio-emotional development. Despite the activities implemented by teachers, some children have problems regulating their emotions, establishing interpersonal relationships and resolving conflicts appropriately. In addition, the limited use of these games and resources limits the opportunities for children to practice skills such as empathy, cooperation and communication. Because of this problem, the research aims to identify how role-playing games contribute significantly to learning and socio-emotional development. The research focuses on a non-probabilistic convenience sample which includes 31 children from Early Childhood Education 2 and a teacher from the same institution. For this purpose, a documentary, field and descriptive research was used, through which valuable information was collected. The qualitative approach was applied, followed by the non-experimental design, that is, only the subject under study was observed and described; as a data collector, an interview and an observation form were carried out. As a result, role-playing games are fundamental tools for the comprehensive development of children, since through them children explore different situations, express their emotions and improve social skills, and through these games children enhance creativity and imagination. It was concluded that role-playing games as a pedagogical strategy are fundamental in early education, which have proven to be important tools for the socio-emotional development of infants.